Treasury of norse mythology eaudiobook Stories of intrigue, trickery, love and revenge. - Napoli, Donna Jo (Recorded Books Inc., 2015)
Classic stories and dazzling illustrations of gods, goddesses, heroes and monsters come to life in a stunning tableau of Norse myths, including those of the thunder god Thor, the one-eyed god and Allfather Odin, and the trickster god Loki. The lyrical storytelling of award-winning author Donna Jo Napoli dramatizes the timeless tales of ancient Scandinavia. This book is the third in the trilogy that includes the popular National Geographic Treasury of Greek Mythology and National Geographic Treasury of Egyptian Mythology.